Equine myeloperoxidase: A novel biomarker in synovial fluid for the diagnosis of infection. (12th November 2012) - Wauters, J.; Pille, F.; Martens, A.; Franck, T.; Serteyn, D.; Gasthuys, F.; Meyer, E.
Summary Reasons for performing study Equine joint infection is a life‐threatening disorder, and confirmation of the diagnosis can be difficult. Synovial fluid biomarkers may assist the discrimination between infectious and noninfectious joint disease. Objectives This study investigates whether the immunological detection of total and enzymatically active myeloperoxidase (MPO) assists the diagnosis of joint infection in horses. Methods The following 4 sample groups were included: healthy; osteochondritis dissecans (OCD); traumatic synovitis; and culture‐confirmed infected joints. Synovial fluid was analysed for total MPO by a horse‐specific sandwich enzyme‐linked immunosorbent assay (ELISA) and for active MPO using the specific immunological extraction followed by enzymatic detection (SIEFED) technique. Western blot analysis was performed to confirm the antibody specificity. Results Synovial fluid from infected joints contained significantly more total and active MPO than samples from healthy joints, joints affected by OCD and joints with traumatic synovitis. Cut‐off values were set at 5000 and 350 ng/ml for total and active MPO, respectively, with fair sensitivity, specificity, positive and negative predictive values and likelihood ratios for infection. Correlation coefficients were reported between the total as well as the active MPO levels and the routine synovial fluid parameters, i.e. the white blood cell count, the neutrophil count and the total protein level. No correlation was observed between MPO and either the age of the horse or the joint affected. Western blotting confirmed the antibody specificity for equine MPO. Conclusions and potential relevance Synovial fluid MPO was identified as a very promising biomarker to augment the discrimination of infectious vs. noninfectious joint disease in horses. Both ELISA and SIEFED techniques can be used for its specific and rapid detection. The analysis of synovial fluid MPO can be used as a complementary test to aid in the discrimination between infectious and noninfectious joint disease, especially when the white blood cell counts and the total protein level are inconclusive.